Imitate Sounds, Onomatopoeia and Interjection in Paremies (on example of Russian and Georgian Proverbs) - Gambashidze, Manana ("Intercultural Dialogues" Transactions, 2021)
In the article there are discussed topics that are less studied in linguistics: Imitate sounds, interjection, onomatopoeia, reflection of productivity in Russian and Georgian proverbs. The results of the study are summarized in tables. The research enables the separation of universals in Georgian and Russian paremies, the presentation of their role in the emotional-aesthetic function of paremies on the basis of analysis and conclusions. It is well known in linguistics that imitate sounds is a well-known method used by the classics, often used by modern poets and writers. In each language, sound imitation has its own peculiarities. Onomatopoeias are lexical units derived from sound imitation phonemes. As for the interjections - this is a universal group of sounds, which expresses the imitation of the emotions of the speaker and is widely used in prose, fables, riddles, poetry. Imitation sounds and interjection are not characterized by morphological features, do not perform a nominative function. All three methods are distinguished by special features for all languages. Our research also confirms their use in Russian and Georgian proverbs, with relatively less productivity.With regard to verbal interjections or onomatopoeia, Russian proverbs stand out especially in bilingual paremies, the number of which is 1-2%, and in proverbs, so-called nouns formed from sound imitation are not found. Another picture is in terms of Georgian proverbs. The percentage of cases of verbal onomatopoeia, in contrast to Russian proverbs, is 7-8%. In Georgian proverbs, the effect of onomatopoeia is enhanced by alliteration, by repetition of the homogeneous consonants.As for the percentages, the following categories of emotional interjections were distinguished in Russian proverbs: irony - 7%, anxiety - 5%, disgust - 2%, ridicule - 8%, desire - 4%. Interjections expressing etiquette were not found in Georgian proverbs, but in Russian it is 4%. In Georgian proverbs we find interjections, expressing irony -6%, anxiety - 8%. Here we mention the types of interjections that are typical, only for Russian or Georgian languages. The isomorphism of interjection in the paremies of both languages ​​is also expressed in their prepositional location. Controversies in the study languages ​​aim not only to distinguish isomorphisms and allomorphisms, but also to establish the universal regularities that are characteristic of the languages ​​of different systems. This diversity is greatly influenced by the identity and universality of each language.